Korean Dream : A Vision for a Unified Korea - Moon, Hyun Jin Preston (New York : Morgan James publishing, 2020)
"An aspirational treatise on nationhood that illustrates why reunification that is led by Korean civil society is the ultimate answer to security, economic, and social problems created through 70 years of division."--page 4 of cover.
Keywords: Korean reunification question (1945- ); Korea -- History -- Partition, 1945